Legacies of Love, Peace and Hope: How Bioethics Education can Overcome Hatred and Divide (Bangladesh Journal of Bioethics, 2020)
In our pursuit of a good life (eubios), both individuals and societies, need to educate themselves on the pursuit of love of life in all domains, self-love, love of others, loving good and love of life.  In this paper I reflect on my own journey through growing up in Christchurch, and experiences around the world, that are the basis for that conclusion.  In our efforts to pursuit bioethics education we can enhance peaceful and harmonius coexistence in our world, through nurturing good decisions that we should all make.